Oleogel: A promising base for transdermal formulations - Balasubramanian, Rajkapoor; Sughir, Abdussalam A; Damodar, Goupale (Asian Journal of Pharmaceutics (AJP), 2014)
Since last two decades the work on oleogels is being exploited in pharmaceutical, cosmetics, and nutraceutical industries for their desired rheological, physical, and chemical stabilities in semisolid formulations. Recently, we had developed a stable and efficacious oleogel containing diclofenac diethylamine for topical application.The present review article deals with the literature of oleogels including its application in various fields from last few decades till date. The literature reveals that the oleogels have simplicity in manufacturing, high physical, chemical, and mechanical stability and better invivo efficacy,which make them appropriate to employ as bases for topical formulations.